The Reflecting Back on the Role of the National Land Agency in Eradicating the Land Mafia - Herlan, Herlan (TABELLIUS: Journal of Law, 2023)
The land mafia is a serious problem that can harm society and the country. As a serious problem, BPN, which is a state instrument in structuring national land law, is mandated to be able to play an active role in eradicating the land mafia. This is yet to be seen, because land mafia cases continue to increase, including in the Kendari City area. The approach method used in this writing is a qualitative method. Based on the studies conducted, it can be understood that the implementation of the BPN's role in efforts to eradicate the land mafia in Kendari City is currently not optimal, this is because the BPN acted after a public complaint regarding a land mafia case in the community. The juridical obstacle is the absence of regulation regarding criminal law enforcement processes in the Technical Instructions of the Ministry of Agrarian Affairs and Land Affairs Number 01/JUKNIS/D.VII/2018 concerning Prevention and Eradication of Land Mafia. The next obstacle is the obstacle in the aspect of law enforcement which consists of internal and external obstacles. Internal constraints are constraints from the BPN institution. External constraints are obstacles related to the legal culture in society related to eradicating the land mafia.Keywords: Agency; Eradication; Land; Mafia.